Post-Independence Mutation and Changes in Media Archives Keeping in Africa: Nigeria's Perspective (2013)
Archives of the media provide an invaluable source of historical and cultural reference materials that could enhance deconstruction of past events in Africa. However, during the post-independent period, media archives suffered neglect and degeneration which could hamper the ability of scholars and historians to reconstruct and interpret historical events that will impact the future of the continent. The nature of media archive is rapidly being transformed by developments in digital technology in the contemporary times with little attention being paid to understanding the implication on Africa. Even though the democratisation of media content is good for democratic participation, there are still ethical questions about what becomes of the media archives in the hands of the untrained since such archives are being rapidly divested from media professionals. The concern here is on threat to the use of such archives for public good and morality since acquisition and retrieval of materials could be done by everyone in the cyber space. It is suggested that policies and institutional mechanisms should be established to manage virtual media archival materials since such materials are going to be subjected to constant changes in format and structure in the digital future